Phorbol Esters Modulate Spontaneous and Ca(2+)-Evoked Transmitter Release via Acting on Both Munc13 and Protein Kinase C - Lou, Xuelin (J Neurosci, 2008)
Diacylglycerol (DAG) and phorbol esters strongly potentiate transmitter release at synapses by activating protein kinase C (PKC) and members of the Munc13 family of presynaptic vesicle priming proteins. This PKC/Munc13 pathway has emerged as a crucial regulator of release probability during various forms of activity-dependent enhancement of release. Here, we investigated the relative roles of PKC and Munc13-1 in the phorbol ester potentiation of evoked and spontaneous transmitter release at the calyx of Held synapse. The phorbol ester phorbol 12,13-dibutyrate (1 μm) potentiated the frequency of miniature EPSCs, and the amplitudes of evoked EPSCs with a similar time course. Preincubating slices with the PKC blocker Ro31-82200 reduced the potentiation, mainly by affecting a late phase of the phorbol ester potentiation. The Ro31-8220-insensitive potentiation was most likely mediated by Munc13-1, because in organotypic slices of Munc13-1(H567K) knock-in mice, in which DAG binding to Munc13-1 is abolished, the potentiation of spontaneous release by phorbol ester was strongly suppressed. Using direct presynaptic depolarizations in paired recordings, we show that the phorbol ester potentiation does not go along with an increase in the number of readily releasable vesicles, despite an increase in the cumulative EPSC amplitude during 100 Hz stimulation trains. Our data indicate that activation of Munc13 and PKC both contribute to an enhancement of the fusion probability of readily releasable vesicles. Thus, docked and readily releasable vesicles are a substrate for modulation via intracellular second-messenger pathways that act via Munc13 and PKC.